2010
DOI: 10.1161/strokeaha.110.578195
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Stroke Symptom Knowledge and Intent to Call 911

Abstract: Background and Purpose-Excessive prehospital delay between acute stroke onset and hospital arrival is an ongoing problem. Translating knowledge of stroke warning signs into appropriate action is critical to decrease prehospital delay. Our objectives were to estimate the proportion of Michigan adults who would react appropriately by calling 911 when presented with hypothetical stroke-related scenarios and to examine the association between knowledge of warning signs and calling 911. Methods-In 2004, questions r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
89
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 30 publications
9
89
1
5
Order By: Relevance
“…Some authors have also showed that despite adequate knowledge of stroke warning signs and intention to immediately activate emergency medical service, in the real scenario a significant number of patients would fail activation of emergency medical service [35,65]. According to ESO only 33-50% of patients recognize their own symptoms as stroke, which might explain the discrepancies between theoretical intended behavior to acute stroke and the reaction in case of an acute stroke [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have also showed that despite adequate knowledge of stroke warning signs and intention to immediately activate emergency medical service, in the real scenario a significant number of patients would fail activation of emergency medical service [35,65]. According to ESO only 33-50% of patients recognize their own symptoms as stroke, which might explain the discrepancies between theoretical intended behavior to acute stroke and the reaction in case of an acute stroke [23].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, increased knowledge of stroke symptoms was not associated with the intent to call 911 for stroke. 4 Finally, patients may not be the only ones delaying care for women compared with men: one recent study showed that among young patients with MI, women were significantly more likely to experience a delay to reperfusion, 20 and other studies have found similar evidence of associations between sex and reperfusion delay as well. 21,22 Additionally, longer symptom-to-presentation time is independently associated with longer presentation-to-reperfusion time, suggesting that delays may beget delays in treatment for MI.…”
Section: Delays In Seeking Carementioning
confidence: 98%
“…3 Knowledge of stroke warning symptoms seems to be similarly limited in both women and men, with 50% to 75% of individuals unaware of important warning symptoms for this condition. 4,5 Of course, women may also be somewhat more likely to experience atypical symptoms, such as nausea, shortness of breath, and back pain in the setting of ischemia, though data are mixed in terms of the degree to which this differs from men's symptom experience, [6][7][8][9] and women with myocardial infarction (MI) are more likely than men to present without chest pain. 10,11 This is particularly important because the absence of chest pain as a presenting symptom has been associated with increased mortality, especially among younger women with MI.…”
Section: Awareness and Recognition Of Cardiac Symptomsmentioning
confidence: 99%
“…Knowledge can be increased with the use of mass media educational campaigns, but such knowledge is not necessarily associated with the intent to call for emergency assistance when symptoms occur. 8 Public education, however, is critical for increasing the demand for services. Additional social-behavioral research is needed to develop a strategy of public education that translates into appropriate action.…”
Section: Maximizing the Use Of IV Tissue-type Plasminogen Activator Wmentioning
confidence: 99%